Grape and wine phenolic composition as a result of training system and canopy modification in Vitis vinifera L.cv Shiraz - De Beer, Petrus Johannes (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.